Decomposition of integrated hybrid life cycle inventories by origin and final-stage inputs - Soo Huey Teh; Thomas Wiedmann (Journal of Economic Structures, 2018)
This note presents a method to decompose life cycle inventories derived from integrated and mixed-unit hybrid life cycle assessment. The approach extends the decomposition method described by Wiedmann (Econ Struct 6:11, 2017. https://doi.org/10.1186/s40008-017-0072-0) by differentiating between impacts from industries, products and processes. The method can be used to quantify the cradle-to-sale impacts of products and processes in the final stage of manufacturing a particular product. We present such a decomposition for the example of life cycle inventories for different types of concrete and compare it to one where the life cycle inventories have been decomposed by origin.
Keywords: 330; Decomposition; Total impact multipliers; Life cycle inventories; Hybrid life cycle assessment; Integrated hybrid LCA; Mixed-unit hybrid LCA; Concrete; Origin; Final-stage inputs